Low-profile metallic tag antenna for UHF-RFID system - Lertsakwimarn, Kittima; Phongcharoenpanich, Chuwong (My University, 2016)
A low-profile ultrahigh frequency (UHF) passive radio frequency identification (RFID) tag for the applications to distinguish metallic from non-metallic is presented. The proposed antenna structure consists of T-shaped structure and parasitic parallel longitudinal strip lines which are placed symmetrically. There is an air gap between the head parts of T-shaped structure for installing IC chip. The head part has shorting pin that connects the ground plane. The parametric studies are described. From the results, the tag antenna with defected ground plane has larger difference of maximum read range compared between the tag on metallic plate and the tag in free space. The proposed UHF-RFID tag antenna can adjust the impedance characteristic by changing the length of the middle longitudinal strip. The tag antenna prototype is fabricated with an area of 90 × 20 × 3 mm3 (0.28λ0 × 0.06λ0 × 0.009λ0). The measured results of maximum read range on the metallic plate and in free space are 83 and 24 mm, respectively. The simulated and measured results of the proposed RFID tag antenna are discussed.
Keywords: Low-profile tag antenna; Metallic tag antenna; UHF-RFID tag antenna